The Effectiveness of Community-Based Health Education on Health Disaster Preparedness Behaviour in Padang Panjang in 2025 - Hajar (Miracle Journal Get Press, 2026)
Increased disaster risk in Indonesia requires strengthening public health preparedness, especially in vulnerable areas such as Padang Panjang. This study aims to analyze the effectiveness of community-based health education on health disaster preparedness behavior in Padang Panjang in 2025 and to examine the mediating role of knowledge, attitude, and self-efficacy. The study used a non-equivalent control group quasi-experimental design with a pre-test and post-test approach. A total of 120 adult respondents were divided into an intervention group (n=60) and a control group (n=60). The intervention was carried out for one month through participatory counseling, group discussions, and preparedness simulations. Data were collected using a structured questionnaire and analyzed using paired t-tests, independent t-tests, and multiple linear regression. The results show a significant increase in knowledge, attitude, self-efficacy, and preparedness behavior in the intervention group (p<0.001), with the largest increase in preparedness behavior (Δ=17.5). There were no significant changes in the control group (p>0.05). Regression analysis showed that knowledge (β=0.32), attitude (β=0.28), and self-efficacy (β=0.41) had a significant effect on preparedness behavior (R²=0.64), with self-efficacy as the dominant predictor. These findings confirm that community-based health education is effective in improving health preparedness by strengthening psychosocial determinants, particularly self-efficacy. The integration of participatory approaches into disaster risk reduction policies is recommended to strengthen sustainable community health resilience in disaster-prone areas.